2014
DOI: 10.1016/s2007-4719(14)70973-1
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of the Good Behavior Game in Classrooms for Children with Delinquent Behavior

Abstract: 2016-03-21T19:08:36

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
23
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 13 publications
5
23
2
Order By: Relevance
“…The current study replicated research showing the efficacy of the GBG for reducing disruptive classroom behavior in an ALC for students with EBD. Our results are consistent with prior research, suggesting the GBG is effective for reducing disruptive classroom behavior with students who have EBD in alternative educational placements (Groves & Austin, ; Joslyn et al, ; Salend et al, ; Sy et al, ). We extended prior research by showing how staff interactions with students changed during the GBG by measuring praise and reprimand statements made by teachers and paraprofessionals.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The current study replicated research showing the efficacy of the GBG for reducing disruptive classroom behavior in an ALC for students with EBD. Our results are consistent with prior research, suggesting the GBG is effective for reducing disruptive classroom behavior with students who have EBD in alternative educational placements (Groves & Austin, ; Joslyn et al, ; Salend et al, ; Sy et al, ). We extended prior research by showing how staff interactions with students changed during the GBG by measuring praise and reprimand statements made by teachers and paraprofessionals.…”
Section: Discussionsupporting
confidence: 91%
“…However, there has not been an empirical evaluation of the effects of the GBG on student–teacher interactions with this population. Salend et al () found that an individualized variation of the GBG was successful in reducing disruption in classrooms in a residential setting for adolescents who were “severely emotionally disturbed.” Joslyn et al () used the GBG to decrease disruption in second‐ through sixth‐grade classrooms in an alternative school for students with EBD and delinquent behavior. Sy, Gratz, and Donaldson () examined different variables that may influence the efficacy of the GBG with students in an alternative school.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, poor treatment integrity did not appear to have an adverse effect the efficacy of the GBG. These results are similar to those of other researchers who demonstrated a treatment effect even when treatment integrity was low (Donaldson et al, ; Joslyn, Vollmer, & Hernández, ; Sy, Gratz, & Donaldson, ).…”
Section: Methodssupporting
confidence: 91%
“…First, the GBG has been extended to undergraduate (Cheatham, Ozga, St. Peter, Mesches, & Owsiany, 2017) and preschool students (e.g., Wiskow, Matter, & Donaldson, 2019). Second, the GBG's effectiveness has recently been demonstrated with a broader array of student populations, including those with emotional and behavioral disorders (EBD) and histories of delinquency in alternativeeducation environments (e.g., Groves & Austin, 2017;Joslyn, Vollmer, & Hernández, 2014). Finally, the GBG has recently been shown to improve previously unexplored behaviors (e.g., undergraduate class participation and physical activity; Cheatham et al, 2017;Galbraith & Normand, 2017).…”
Section: Novel Populations Settings and Behaviorsmentioning
confidence: 99%